Peran brand ambassador, brand love, dan kualitas produk terhadap keputusan pembelian skincare skintific pada mahasiswa S1 universitas dian nuswantoro semarang - Sarah Nurrohamah; Handy Nur Cahya; Vincent Didiek Wiet Aryanto; Amalia Nur Chasanah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Awareness regarding the importance of skin health makes people care and look for the best care products. Skintific has emerged as a brand that is much loved by the public and has a wide market. To determine the influence of Brand Ambassador, Brand Love, and Skintific Product Quality on purchasing decisions among students at Dian Nuswantoro University, Semarang. Quantitative Data, analysis using Smart-PLS. The research sample was 154 respondents using Purposive sampling. Results: H1 is rejected, namely Brand Ambassador does not influence Purchasing Decisions with a p value of 0.972, H2 is accepted, namely Brand love has a positive effect on Purchasing Decisions with a p value of 0.001, H3 is accepted, namely Product quality has a positive effect on Purchasing Decisions with a p value of 0.001, H4 is accepted, namely Brand Ambassador, Brand love, and Product Quality simultaneously have a positive and significant effect on Purchasing Decisions by 61.6%. Conclusion: Brand Ambassador does not affect Purchasing Decision; Brand love has a positive effect on Purchasing Decision; Product quality has a positive effect on Purchasing Decision; Brand Ambassador, Brand love, and Product Quality simultaneously have a positive and significant effect on Purchasing Decision